First‐trimester prediction of surgical outcome in abnormally invasive placenta using the cross‐over sign. (5th January 2018) - Calì, G.; Forlani, F.; Minneci, G.; Foti, F.; Di Liberto, S.; Familiari, A.; Scambia, G.; D'Antonio, F.
ABSTRACT: Objective: Ultrasound assessment of the relationship between the ectopic gestational sac and the endometrial line (cross‐over sign; COS) in Cesarean scar pregnancy (CSP) has been shown to be useful in predicting the evolution of CSP towards different types of abnormally invasive placenta (AIP). The aim of this study was to ascertain whether the COS can be used to predict surgical outcome in women with AIP. Methods: A retrospective analysis was performed of early first‐trimester (6–8 weeks' gestation) ultrasound images of women with AIP managed in the third trimester of pregnancy. We hypothesized that assessment of COS may identify cases of AIP at higher risk of intra‐ or postsurgical morbidity. Outcomes explored were estimated blood loss during surgery, need for and amount of packed red blood cells and fresh frozen plasma units required either during or after surgery, operative time, intrasurgical complications, gestational age at birth, delivery < 34 weeks of gestation, length of hospital stay and admission to intensive care unit. Differences in the explored outcomes were assessed among women with different types of COS variant (COS‐1, COS‐2+ or COS‐2−) as observed on first‐trimester ultrasound examination. Results: Sixty‐eight pregnancies were included in the study. Mean estimated blood loss was higher in AIP pregnancies with COS‐1 than in those with COS‐2+ ( P = 0.039) or COS‐2− ( P = 0.01). Mean number of packed red blood cell units required during or after the operation was higher in women with COS‐1 compared with those with COS‐2+ ( P = 0.001) and COS‐2− ( P = 0.029), while there was no difference between pregnancies with COS‐2+ and those with COS‐2− ( P = 0.797). Mean operative time was longer in AIP pregnancies with COS‐1 than in those with COS‐2+ ( P = 0.039) or COS‐2− ( P = 0.017). Finally, pregnancies with COS‐1 were delivered earlier than those with COS‐2+ ( P = 0.0001) or COS‐2− ( P = 0.0001). Conclusion: First‐trimester ultrasound assessment of the relationship between the ectopic gestational sac and the endometrial line (COS) may identify women with AIP who are at higher risk of intra‐ or postsurgical morbidity. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations. This article has been selected for Journal Club. Clickhere to view slides and discussion points.